Георгій Косміаді: художник між Сходом і Заходом - Костюк, Л. (Народознавчі зошити, 2012)
У статті розглядаються особливості життя і творчості Георгія Косміаді (1886—1967). Обґрунтовується художня система митця, в якій органічно переплелися естетичні традиції східної та західної культур. Спадщина Г. Косміаді (понад 5000 картин) сьогодні вписується в контекст історії мистецтва ХХ століття. In the article have been considered some circumstances of an artist Heorhii Kosmiadi’s (1886—1967) life and creative work are examined considered in the article. The painter’s artistic system, in which had quite organically been interwoven aesthetic traditions of Western and Eastern cultures, has been discovered and represented. H. Kosmiadi’s artistic heritage (more 5 thousand paintings) has naturally entered into the context of art history of XX c. В статье рассматриваются особенности жизни и творчества Георгия Космиади (1886—1967). Раскрывается его художественная система, в которой органически переплелись эстетические традиции восточной и западной культуры. Наследие Г. Космиади (более 5000 картин) сегодня вписывается в контекст истории искусства ХХ столетия.